MR Angiography of the Adamkiewicz Artery and Anterior Radiculomedullary Vein: Postmortem Validation - Nijenhuis, R.J.; Jacobs, M.J.; van Engelshoven, J.M.A.; Backes, W.H. (American Journal of Neuroradiology, 2006)
SUMMARY: Spinal cord arteries and veins are difficult to visualize and distinguish by MR angiographic techniques because of their small sizes, similar spatial course, and close vascular anatomy. Contrast-enhanced MR angiography was demonstrated to dynamically resolve the Adamkiewicz artery from the anterior radiculomedullary vein in the thoracolumbar spinal cord. The location of the Adamkiewicz artery and the anterior radiculomedullary vein could be validated in the postmortem specimen of a thoracoabdominal aortic aneurysm patient.